Identification of differentially expressed proteins in the testes of normal yaks and sterile hybrids by two-dimensional electrophoresis and mass spectrometry - FU, WEI; LI, CAIXIA; LIU, WENJING; MA, XIAOQIN; QIU, XIANG; REN, LIANG; HUANG, LIN; JIN, SUYU; ZHENG, YUCAI (The Indian Journal of Animal Sciences, 2015)
The study was conducted to compare differentially expressed proteins in the testes of adult yaks (Bos grunniens) and sterile cattle-yaks, in order to elucidate mechanisms of hybrid male sterility. Total proteins were extracted from testes and subject to 2-dimensional electrophoresis and mass spectrometry identification. A total of 19 differentially expressed proteins were identified, of which 13 were downregulated and 4 upregulated in cattle-yak testes. Interestingly, two chaperones (T-complex protein 1 and peptidyl-prolyl cis-trans isomerase) with decreased expressions in the testes of cattle-yaks were revealed, however, their association with the hybrid sterility is unclear. Protein phosphatase methylesterase-1 was decreased by over 8-folds in the testes of cattle-yaks than yaks, and may be associated with cell cycle arrest during spermatogenesis. Several proteins involved in male fertility and/or energy metabolism were also identified, such as mitochondrial peroxiredoxin-5 and sorbitol dehydrogenase. In addition, N (G), N (G)-dimethylarginine dimethylaminohydrolase (DDAH), which can increase the production of nitric oxide and affect normal spermatogenesis in testis, was upregulated in cattle-yak testes. The increased expression of DDAH is probably associated with male sterility of cattle-yaks. The results of this study suggest that the mechanisms of male sterility of cattle-yaks might be associated with many proteins of diverse functions, and some proteins such as chaperones and testis-specific proteins may play important roles.